Current Trends in Software Engineering Research - Vijiyan, Gayatri (Review of Computer Engineering Research, 2015)
Software engineering is dynamic disciplines that have continuous growth in research in identifying new methods, tools and methodologies that have cause vast improvement in software development and maintenance to be more reliable and efficient. Past research critics on cost reduction, quality and flexibility have endless try to design and develop many ways to improve these sectors are still causing impacts to the software industry [1]. The new trends in software engineering research topics resolves under the research field of Cloud Computing, Big Data, Android Computing, Network Security and Software Engineering Project Management. Nevertheless, there are more other research areas in software engineering that have been intense researched and implemented in the industries.